STRATEGI KOMUNIKASI YAYASAN LINGKAR PERDAMAIAN DALAM MELAKSANAKAN DERADIKALISASI TERHADAP MANTAN NARAPIDANA TERORIS - Imam safii imam safii (Jurnal Dakwah: Media Komunikasi dan Dakwah, 2019)
This paper presents itself as a criticism of the war on terrorism in Indonesia by taking action and enforcing the law, mobilizing the police apparatus especially Detachment88 and carrying out executions of radical perpetrators. It turns out that the handling has not solved the problem of terrorism that occurred in Indonesia. It could even give birth to a new terrorism from the family of the naples as well as the ex-Napites from prison due to their grudges. So from this the need for handling a soft power approach is to strive for the de-radicalization of ex-convicted terrorists in the hope of preventing the emergence of new terrorists in the next era. The Circle of Peace Foundation is a foundation founded by Ali Fauzi along with former terrorists. This foundation is one of the foundations in the field of Flow Integrity control with the aim of changing the mindset of families of ex-terrorist convicts - former Islamic terrorists are friendly rather than angry and keep them away from destructive attitudes. Ali Fauzi as the chairman gathered a number of ex-combatants and invited them together to echo the values of world trade. The purpose of this study is to find out about the communication strategies of the Foundation's circle of peace actions in carrying out de-alienation of ex-convicted terrorists. Decalcalized by this circumference foundation, the Soft Power Apoach model is a soft method which is then implemented with a communication strategy. So the results obtained from the communication strategy of the circle of peacekeeping circles are by establishing reliable communicators and partners in their fields, setting targets of de-decalalized programs, namely changing structuralist mindset towards constructive, compiling peaceful messages and choosing social media as a means of disseminating decalecalized information implemented by foundations peramayan circle.